Protected areas still used to produce Brazil's cattle. Issue 6 (17th October 2022) - West, Thales A. P.; Rausch, Lisa; Munger, Jacob; Gibbs, Holly K.
Abstract: Cattle production inside Brazil's protected areas (PAs), including indigenous lands, continues to contaminate Amazonian supply chains more than a decade after efforts to reform the sector were launched with the signing of the zero‐deforestation cattle agreements (CAs). During 2013–2018, nearly 1.1 million cattle head were sold directly from private properties inside PAs to slaughterhouses in Mato Grosso, Pará, and Rondônia states. Another 2.2 million head were linked via indirect suppliers located in PAs. Most of these 3.3 million slaughtered head were originated in to sustainable‐use areas (72%), where cattle ranching may be permitted in certain cases; however, production also occurred in strictly protected units (20%) and indigenous lands (8%), where commercial grazing activities are illegal and prohibited by the CAs. Nearly half of the PA properties linked to cattle transactions from 2013 to 2018 also had deforestation. We estimate that approximately 2.8 million cattle head from properties in PAs were sold to slaughterhouses participating in the CAs (86% of the total cattle from indirect suppliers in PAs). Controlling commercial cattle production inside of PAs is crucial to both ensure Brazil's access to international beef markets and protect critical biodiversity regions in the Amazon rainforest.